PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN TERHADAP DEPOT AIR MINUM ISI ULANG BERDASARKAN PUTUSAN MENTERI PERINDUSTRIAN DAN PERDAGANGAN NOMOR 651/MPP/KEP/10/2004TENTANG PERSYARATAN TEKNIS DEPOT AIR MINUM DAN PERDAGANGANYA - Asram A.T.Jadda, Ichsanullah, Aliah (FAKULTAS HUKUM UM PAREPARE, 2020)
This study aims to determine the licensing procedure for the establishment of drinking water depots and how to monitor drinking water depots carried out by the industry and trade. In this study the authors used the normative method. The data obtained by the author is from primary legal materials, namely laws and regulations regarding drinking water depots and tertiary legal materials. The data collection technique used is literature study. The data analysis technique used is descriptive qualitative. Based on the decision of the minister of industry and trade number 651 / MPP / Kep / 10/2004 regarding the technical requirements of drinking water depots and their trade, to establish a drinking water depot there are 3 requirements that must be met, namely industrial registration certificate and trading business registration certificate, water supply guarantee letter. standards from the regional drinking water company, and a hygiene-worthy certificate. Based on the verdict, supervision of drinking water depots, namely supervision of the use of raw water, production processes, machines and equipment as well as trading is carried out periodically or the time required. And supervision of the quality of drinking water depot production is carried out by a drinking water quality inspection laboratory appointed by the government. The result of this research is that in establishing a drinking water depot, only two requirements are needed, namely aindustry and registrationtrade businesscertificate ofregistration certificate, and a certificate of proper hygiene. As well as the lack of supervision carried out by related agencies and from the owner of the drinking water depot. What should be checked periodically, but not done by the drinking water depot and from the industry and trade office.